Genetic diversity analysis in tamarind (Tamarindus indica L.) - M H Savita, K Krishnamurthy, S Hittalama, S Gangaprasad, R Rajkumar, R L Ravikumar (Journal of Spices and Aromatic Crops, 2013)
The present study conducted at Shimoga (Karnataka) during 2005–2008 is an attempt to examine genetic relatedness and genetic diversity among 13 Indian collections of Tamarind. Twenty eight selected arbitrary primers were used for characterization using RAPD that generated 131 fragments, of which 116 (88.54%) were polymorphic. Two genotypes, NTI62 and NTI84 were distinguished by unique band specific to them. The genetic similarity coefficient values suggested a wide genetic base for genotypes considered for the study. Cluster analysis based on unweighted pair group method using arithmetic average (UPGMA) clearly indicated that genotypes did not cluster according to their site of collection. This could be attributed to highly cross pollinating nature, small distribution area and that most tamarind genotypes grown in India are from seed source.